Assessment of Water Quality in Water Intake Points the City of Grozny by Biotesting Methods - Ataeva Aminat; Muzakaeva Khava; Malika Vakaraeva (BIO Web of Conferences, 2023)
A study of 184 water samples in the water intake areas of the city of Grozny (Goity, Sunzhensky and Chernorechensky) was carried out using generally accepted biotesting methods. Luminescent bacteria E. coli and freshwater crustaceans Daphnia magna Straus were used as test objects. The toxicity of samples from the Sunzha water intake in the summer period during biotesting on bacteria and a different degree of chronic toxicity of water samples during biotesting of water on daphnia, depending on the place of water intake, are shown.